(untitled) (European Journal of Pure and Applied Mathematics, 2022)
The coefficient conjugate serves as the foundation for many conjugate gradient methods. The quadratic model is used to derive a novel coefficient conjugate in this study. Its global convergence result might be produced under Wolfe line search circumstances. The conjugate gradient method’s performance for unconstrained optimization problems is demonstrated through numerical tests.